2020
DOI: 10.1145/3365668
|View full text |Cite
|
Sign up to set email alerts
|

Transparency about a Robot's Lack of Human Psychological Capacities

Abstract: The increasing sophistication of social robots has intensified calls for transparency about robots' machine nature. Initial research has suggested that providing children with information about robots' mechanical status does not alter children's humanlike perception of, and relationship formation with, social robots. Against this background, our study experimentally investigated the effects of transparency about a robot's lack of human psychological capacities (intelligence, self-consciousness, emotionality, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Some children, who lean towards transparency by asking de-anthropomorphizing questions, try to situate robots at the lower end of the human-likeness scale. Previous research has shown that transparency decreased the children's humanlike perception of the robot in terms of animacy, anthropomorphism, social presence and perceived similarity [89]. In our research, children made assumptions regarding its movement abilities, mechanical equipment, gender, experience, knowledge, etc.…”
Section: Possible Signs Of Expectations Towards the Robotmentioning
confidence: 78%
See 1 more Smart Citation
“…Some children, who lean towards transparency by asking de-anthropomorphizing questions, try to situate robots at the lower end of the human-likeness scale. Previous research has shown that transparency decreased the children's humanlike perception of the robot in terms of animacy, anthropomorphism, social presence and perceived similarity [89]. In our research, children made assumptions regarding its movement abilities, mechanical equipment, gender, experience, knowledge, etc.…”
Section: Possible Signs Of Expectations Towards the Robotmentioning
confidence: 78%
“…These questions to Pepper suggest trust towards the robot's skills and abilities, and children's willingness to engage in a joint play. As previous studies [89] point out, higher transparency of the robot's lack of psychological capabilities (e.g., a lack of preferences or knowledge of social rules) negatively affects the formation of child-robot relationship in terms of the trust, whereas the children's feelings of closeness remain unaffected. For this reason, an analysis of closeness-related behaviors and actions of children during CRI that indicate children's trust towards the robot is a key factor in the interaction design.…”
Section: (D)mentioning
confidence: 84%
“…Turkle (2007) has argued that children bond with relational artifacts "not because of what these objects [can] do (physically or cognitively) but because of the children's emotional connection to the objects and their fantasies about how the objects might be feeling about them" (Turkle 2007, p. 507). In contrast to this statement, a recent study (van Straten et al 2020c) found that children trusted a robot less when they were made aware of its lack of human psychological capacities (i.e., intelligence, selfconsciousness, emotionality, identity construction, and social cognition). Still, in the present study, children tended to be aware of the robot's lack of autonomy and human-likeness but tended not to care about it.…”
Section: Effects Of Transparent Teleoperationmentioning
confidence: 80%
“…A recent study found that children's awareness of a social robot's lack of humanlike psychological capacities (i.e., capacities of 'mental others') decreased children's ratings of a robot's animacy, anthropomorphism, social presence, and perceived similarity to the self, as well as children's trust in the robot (van Straten et al 2020c). Thus, informing children about a robot's technological rather than human like status alters children's robot perceptions and affects childrobot relationship formation at least partially.…”
Section: (Transparent) Teleoperation In Crimentioning
confidence: 99%
“…Consequently, transparency in automation cognitive functioning may help people to increase human-like attributions. A recent study shows that transparency about the robot's lack of human psychological processes and abilities reduced children's anthropomorphic tendencies and trust (van Straten et al, 2020). Therefore, transparency may improve automation anthropomorphism, and as described before, automation anthropomorphism influences trust.…”
Section: May Automation Inner Speech Affect Human Trust?mentioning
confidence: 81%